Towards curriculum implementation: examining business management teachers’ teaching efficacy beliefs - Leticia Bosu; Edmond Kwesi Agormedah (Discover Education)
Abstract Drawing from Social Cognitive Theory (SCT), this inquiry examined Business Management teachers’ (BMTs) teaching efficacy beliefs in curriculum implementation at the senior high school (SHS) level. Using a descriptive, cross-sectional survey design, 105 BMTs were conveniently selected from 43 public SHS in the Greater Accra Region of Ghana. The data was collected using the Business Management Teaching Efficacy Belief Questionnaire (BMTEBQ-12). The data gathered was processed and analysed using SPSS version 25.0 and Analysis of Moment Structures (AMOS version 23.0), producing descriptive statistics (means and standard deviations) and further analytic techniques including repeated-measures ANOVA and factorial MANOVA. The study discovered that BMTs were highly efficacious in implementing the curriculum. They highly demonstrated efficacy beliefs in classroom management (ECM). Statistically, age influences BMTs’ teaching efficacy beliefs in curriculum implementation. BMTs’ teaching efficacy beliefs in curriculum implementation do not vary based on gender and teaching experience. The findings have implications for educational policy makers to continue providing relevant, ongoing and sustained continuous professional development opportunities on teachers’ instructional pedagogical practices towards curriculum implementation.